CONCEPTUAL ISSUES RELATED TO LEGAL SELF-REGULATION IN THE FIELD OF GENOMIC RESEARCH IN RUSSIA - Viktorovna Mashkova, Kseniya; Viktorovna Varlen, Mariya; Sergeevich Zenin, Sergey; Nikolaevich Suvorov, Georgiy; Yur'yevich Shirokov, Aleksey (Gênero & Direito, 2020)
Currently, the human genome is actively studied and these study results are often regarded by society as revolutionary. However, scientists involved in such research make different forecasts regarding its future achievements and practical application. This significantly complicates the process of setting certain limits to relations that should be legally regulated and protected. These arguments are justified by the legal support of the relevant relations in some countries. The article analyzes the basic guidelines developed by professional genetic associations at the international level and draws several significant conclusions that define the conceptual foundations of the self-regulation of genomic research in the Russian Federation. The study aims at considering the Russian legal mechanism of self-regulation in the field of genomic research. Its methodological basis is the theory of knowledge and the universal method of materialist dialectic. The authors of the article also use such general scientific methods as formal-logical and systematic methods, description, observation, comparison, analysis and synthesis. They have concluded that it is necessary to enshrine several provisions and professional requirements for self-regulatory communities: compliance with ethical standards in scientific research; informing (both the population and medical community) through the implementation of educational programs; correlation of genomic studies with good clinical practice and evidence-based medicine; consideration of the study results of the human genome as personal data; differentiation of medical and non-medical activities in the field of genome.